PENGARUH KETERAMPILAN GURU MEMBERIKAN PENGUATAN TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Elda Kholidah Hsb; Arfin Hasibuan; Irma Sari Daulay; Nurhalimah Harahap (Titik Fokus Karya, 2025)
The purpose of this study was to determine 1) the effect of creativity in providing reinforcement to the learning motivation of class III students of MIN Sibuhuan. 2) How much influence does creativity provide reinforcement to the learning motivation of class III students of MIN Sibuhuan. This study is a quantitative study, the population in the study were all class III students of MIN Sibuhuan, while the sample in the study was taken from the entire population, with a total of 28 students. Data collection techniques used questionnaires and documentation. Data analysis techniques used descriptive statistics and prerequisite tests. The results obtained were that the normality test showed that all data obtained by the researcher had normal data because lhitung <ltabel with a value of 0.999 <0.1772 on the variable providing reinforcement and on the variable learning motivation 0.0010 <0.1772. And the homogeneity test showed that the value of fhitung <ftabel with a value of 0.672 <4.23. providing reinforcement has a significant effect on the learning motivation of MIN Sibuhuan students. Based on the results of the t-test, it shows that the t-count value > t-table (3.624 > 1.705), and the significant value is 0.000 < 0.05. This means that the Ha hypothesis is accepted and H0 is rejected. then the determination test shows a value of 0.549 or 54.9%. meaning that the skill of providing reinforcement can contribute to increasing student learning motivation by 54.9% while 45.1% is explained by other variables that are not studied.